Analysis of academic service information systems on the satisfaction of Sukarobot partners using the Servqual method - Rahma, Retno Sabrila; Sembiring, Falentino; Sihabudin, Sihabudin (Universitas Muhammadiyah Riau, 2026)
The development of information technology has significantly impacted the improvement of service quality in the education sector, particularly in academic services. Sukarobot utilizes an academic service information system to support its service delivery to partners. However, several obstacles have been encountered in its implementation, such as occasional system errors, delayed service responses, and suboptimal service quality that meets user expectations. Therefore, this study aims to analyze the quality of the academic service information system and its impact on Sukarobot partner satisfaction using the SERVQUAL method. This study employed a quantitative approach, with data collection techniques involving the distribution of questionnaires to Sukarobot partners. The SERVQUAL method measures service quality based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were analyzed using validity tests, reliability tests, Likert scale analysis, and gap analysis between user perceptions and expectations. The results showed that all questionnaire items were valid, as their calculated r values ​​were greater than the tabulated r values ​​of 0.2133. Furthermore, the reliability test results showed that all variables had Cronbach's Alpha values ​​above 0.60, thus declaring the research instrument reliable. Based on the SERVQUAL analysis, all dimensions had negative gap values, indicating that the service quality of Sukarobot's academic information system has not fully met user expectations. The assurance dimension had the smallest gap value of -0.34, while the reliability and responsiveness dimensions had the largest gap values ​​of -0.40, making them a top priority for improvement